Network Design Issues in Wireless Body Area Network - Sunil Kumar Nandal, (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
This paper presents a survey on various aspects of Wireless Body Area Network (WBAN) and its utility in healthcare system. Along with applications of WBAN in healthcare different areas of research with other prospective opportunities and prominent challenges are also discussed. Development in the field of wireless communication, particularly in the field of Personal Area Network and mobile networks, has lead to development of mobile healthcare system. As WBAN essentially consist of body sensors to sense various physical properties related to health. Apart from applications of WBAN, communication in WBAN and other important aspects like security, scalability are discussed. Some of the other important issues are physical and MAC layer design and network protocols being analysed.